Tracking Network Salience: A Transnational Study of Inter-Media Agenda-Setting in the Iranian-American Crisis 2020 - Shimaa H.A. Mohammed; Guido Keel; May O.S. Ahmed; Adel R.A. Mustafa (Romanian Journal of Communications and Public Relations)
The present study investigated the international intermedia network agenda setting among eleven news websites from four different languages and three political orientations, in the aftermath of the assassination of Iranian General Qasem Soleimani. Our study aimed to explore the potential for a given medium to shape the agenda of other countries’ media, and to identify if language or political orientation may influence intermedia network agenda setting at both the issue and attribute levels.